Edukasi Perubahan Psikologis Pada Masa Kehamilan - Amara Celeste Jade (Lembaga Pengembangan Kinerja Dosen, 2024)
Pregnancy is a physiological and normal process that not only involves the biological aspects of a woman's life but also psychological, emotional, and spiritual aspects. A woman must fulfill her role as a mother during pregnancy. This service is carried out at the Jampandanbar Community Health Center to provide information about pregnancy, various psychological changes during pregnancy, and psychological adjustments during pregnancy to take on the role of a mother. The number of participants in this service activity was 20 people, held on November 21 2020 at the Taro District Office with a lecture, question and answer and interaction format. The results of this activity show behavioral changes in the form of successful adaptation, especially psychological changes during pregnancy.